Influencer marketing in the digital environment: analysis of its factors, generational impact, and ethical considerations. - Alcántara-Hernández, Ruth Josefina (2025)
ABSTRACT Introduction. Influencer marketing, consolidated in the digital environment, is based on the credibility and closeness of opinion leaders with their audiences. The problem lies in the lack of regulation and the vulnerability of minors to covert advertising. Its study is relevant to understanding its influence on perceptions, consumption habits, and socialization, integrating social learning and reinforcement theories. Objective. To analyze the factors influencing influencer marketing in Mexico, its intergenerational impact, and the ethical risks for child and youth audiences. Method. Two studies were integrated. The first (2021) was a qualitative–phenomenological study with interviews, observation, and a discussion group on micro-influencers and brands, analyzed in ATLAS.ti. The second (2023) employed a mixed methodology, with surveys and focus groups involving 26 children from Hidalgo aged 8 to 12, analyzed with MAXQDA, considering digital habits, perceived credibility, and consumption. Results. Findings show that authenticity and value alignment between brand and influencer are decisive in generating engagement. Children recognize and adopt expressions and products from their favorite creators, though they struggle to distinguish between advertising and organic content. Among adults, influencers provide visibility and positioning but do not guarantee direct sales. Discussion and conclusions. Influencer marketing functions as a mediator in the construction of emotional bonds, credibility, and brand awareness. However, its success depends on strategic planning and the ethical selection of collaborators. In the case of minors, influence impacts identity, language, and consumption, confirming the need for critical digital education and advertising regulation. Understanding these dynamics is essential to balance commercial opportunities and social risks in the digital environment within the consumer decision-making process.